BUILDING A HEALTHY COMMUNITY BY IMPROVING THE HEALTH OF THE ELDERLY IMPLEMENTATION THE DIARII PROGRAM IN SOUTH KALIMANTAN - Unja, Ermeisi Er; Oktovin; Rachman, Aulia; Warjiman; Mallisa, Hilda Emma (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Hypertension is still one of the most common diseases among the elderly. One of the areas where hypertension cases are still high is South Kalimantan. The elderly need internal and external support as a preventive measure to avoid further consequences of hypertension. The role of cadres in this case is very important to provide education about hypertension in the elderly. Community service was carried out with the aim of improving the quality of cadres in the care of the elderly, especially those suffering from hypertension, whose activities were carried out on 26 May 2023. The participants in this activity were 15 cadres and 40 elderly people. The activities were carried out for 3 weeks. The first week, the cadres were trained in gerontic care. The second week, the elderly hypertension and their families were counseled during the implementation of the DIARII programme. The third week, the elderly gymnastics activities were carried out. The service activities carried out received a positive response from the cadres and the community, considering that this is an effort to improve the performance of the cadres and to improve the quality of life of elderly groups with hypertension.